2016
DOI: 10.1177/0261927x16654735
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Homophobic Labels on the Internalized Homophobia and Body Image of Gay Men: The Moderation Role of Coming-Out

Abstract: This study investigates whether homophobic labels and category-neutral terms are differently appraised as a function of levels of coming-out. After reporting their coming-out status, participants were exposed to either homophobic or category labels and reported their semantic associations, level of internalized homophobia, and body perceptions. Results show that labels were more positively evaluated as participants’ coming-out increased. High–coming-out individuals reported higher internalized homophobia and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
15
0
3
Order By: Relevance
“…Archival data analyses conducted by Mullen and Smyth (2004) revealed that immigrant minorities' suicide rate is strongly predicted by the negativity of the ethnophaulisms used to describe the minority (which was derived from the historical record of hate speech in the United States). An Italian study, in which gay people were exposed to homophobic labels (Bianchi, Piccoli, Zotti, Fasoli, & Carnaghi, 2017) found that homosexual individuals (particularly those who were open with their identity) reported higher levels of internalized homophobia after being confronted with such labels. Interestingly, the reverse pattern was observed for those participants who were hiding their gay identity.…”
Section: Hate Speech Deteriorates Well-being: the Minority Perspectivementioning
confidence: 99%
“…Archival data analyses conducted by Mullen and Smyth (2004) revealed that immigrant minorities' suicide rate is strongly predicted by the negativity of the ethnophaulisms used to describe the minority (which was derived from the historical record of hate speech in the United States). An Italian study, in which gay people were exposed to homophobic labels (Bianchi, Piccoli, Zotti, Fasoli, & Carnaghi, 2017) found that homosexual individuals (particularly those who were open with their identity) reported higher levels of internalized homophobia after being confronted with such labels. Interestingly, the reverse pattern was observed for those participants who were hiding their gay identity.…”
Section: Hate Speech Deteriorates Well-being: the Minority Perspectivementioning
confidence: 99%
“…Together, these tools are urgently needed given the detrimental consequences that 18" homophobic bullying and harassment have on the victim's well-being (e.g., depression, 19" psychological distress, and low self-esteem; Bianchi, Piccoli, Zotti, Fasoli, & Carnaghi, 2017;20" Bontempo & D'Augelli, 2002;Collier, Van Beusekom, Bos, & Sandfort, 2013;Swearer, Turner, 21" Givens, & Pollack, 2008;Wyss, 2004), and scholastic success (e.g., school absenteeism, discipline 22" problems, and a low level of school belonging; Kosciw et al, 2016;Rivers, 2000;Poteat & 23" Espelage, 2007).…”
Section: "mentioning
confidence: 99%
“…Frequent usage of homophobic epithets has subtly trained individuals to marginalise LGBT people, just like frequent usage of cardinal points trains orientation. Several empirical studies found a significant correlation between exposure to homophobic insults and homophobia (Burn 2000;Carnaghi and Maass 2007;Bianchi et al 2017), corroborating the theoretical proposition that language shapes thought. Not only this phenomenon hurts a sizeable minority, but it also legitimises an unconscious form of violence and marginalisation, reinforcing a sociocultural barrier based on conformation to heteronormative standards.…”
Section: Introductionmentioning
confidence: 56%